The Staphylococcus aureus extracellular matrix protein (Emp) has a fibrous structure and binds to different extracellular matrices. Issue 1 (December 2017) - Geraci, Jennifer; Neubauer, Svetlana; Pöllath, Christine; Hansen, Uwe; Rizzo, Fabio; Krafft, Christoph; Westermann, Martin; Hussain, Muzaffar; Peters, Georg; Pletz, Mathias; Löffler, Bettina; Makarewicz, Oliwia; et al.
Abstract The extracellular matrix protein Emp ofStaphylococcus aureus is a secreted adhesin that mediates interactions between the bacterial surface and extracellular host structures. However, its structure and role in staphylococcal pathogenesis remain unknown. Using multidisciplinary approaches, including circular dichroism (CD) and Fourier transform infrared (FTIR) spectroscopy, transmission electron (TEM) and immunogold transmission electron microscopy, functional ELISA assays andin silico techniques, we characterized the Emp protein. We demonstrated that Emp and its truncated forms bind to suprastructures in human skin, cartilage or bone, among which binding activity seems to be higher for skin compounds. The binding domain is located in the C-terminal part of the protein. CD spectroscopy revealed high contents of β-sheets (39.58%) and natively disordered structures (41.2%), and TEM suggested a fibrous structure consisting of Emp polymers. The N-terminus seems to be essential for polymerization. Due to the uncommonly high histidine content, we suggest that Emp represents a novel type of histidine-rich protein sharing structural similarities to leucine-rich repeats proteins as predicted by the I-TASSER algorithm. These new findings suggest a role of Emp in infections of deeper tissue and open new possibilities for the development of novel therapeutic strategies.